Macro‐ and Nano‐Porous 3D‐Hierarchical Carbon Lattices for Extraordinarily High Capacitance Supercapacitors. (21st April 2022) - Katsuyama, Yuto; Haba, Nagihiro; Kobayashi, Hiroaki; Iwase, Kazuyuki; Kudo, Akira; Honma, Itaru; Kaner, Richard B.
Abstract: Supercapacitors, which can be charged/discharged rapidly, play important roles in a sustainable society. Thick electrodes can reduce the ratio of inactive components in the overall cell while simultaneously improving energy and power densities. However, thick electrodes induce longer ion diffusion pathways, and capacitance drops dramatically after a certain thickness. To overcome this, precisely designed macro‐ and nano‐porous 3D‐hierarchical carbon lattices, where ions can diffuse freely inside the electrode, are prepared by combining an inexpensive stereolithography‐type 3D printer, whose resolution is 50 µm, with a simple CO2 activation process. The activated 3D carbon lattice with a 66% burn‐off ratio (3D‐CL‐A66%) has ordered macropores (≈150 µm) and uniform nanopores (2–3 nm), exhibiting a maximum areal capacitance of 5251 mF cm –2 at 3 mA cm –2 . Furthermore, manganese oxide is electrochemically deposited on 3D‐CL‐A16% for 8 min (3D‐CL‐A16%‐MnO2 ‐8 min),  increasing the areal capacitance by 2.5‐times. Finally, an all‐3D‐printed asymmetric 1.8 V supercapacitor is prepared by combining 3D‐CL‐A16%‐MnO2 ‐8 min and 3D‐CL‐A66% as the positive and negative electrodes, respectively, demonstrating a maximum energy density of 0.808 mWh cm –2 at a power density of 2.48 mW cm –2 . The achieved values are one of the highest areal energy and power densities reported so far. Abstract : A 3D‐hierarchical carbon lattice with ordered macropores (≈150 µm) and uniform nanopores (2–3 nm) for supercapacitor electrodes is successfully prepared using an inexpensive 3D printer and a simple gas activation process. The 3D‐ordered macropores facilitate ion transport inside the thick electrodes. The achieved areal energy and power densities are among the highest values reported to date.